Clinical implications of interstitial pneumonia with autoimmune features diagnostic criteria in idiopathic pulmonary fibrosis: A case control study - Tomassetti, Sara; Ravaglia, Claudia; Puglisi, Silvia; Wells, Athol U.; Ryu, Jay H.; Bosi, Marcello; Dubini, Alessandra; Piciucchi, Sara; Girelli, Francesco; Parronchi, Paola; Lavorini, Federico; Rosi, Elisabetta; et al. (Frontiers in Medicine, 2023)
Background A subgroup of IPF patients can meet IPAF criteria (features suggesting an underlying autoimmune process without fulfilling established criteria for a CTD). This study was aimed to evaluate whether IPAF/IPF patients compared to IPF patients differ in clinical profile, prognosis and disease course. Methods This is a retrospective, single center, case–control study. We evaluated 360 consecutive IPF patients (Forlì Hospital, between 1/1/2002 and 28/12/2016) and compared characteristics and outcome of IPAF/IPF to IPF. Results Twenty-two (6%) patients met IPAF criteria. IPAF/IPF patients compared to IPF were more frequently females (N = 9/22, 40.9% vs. N = 68/338, 20.1%, p = 0.02), suffered more frequently from gastroesophageal reflux (54.5% vs. 28.4%, p = 0.01), and showed a higher prevalence of arthralgias (86.4% vs. 4.8%, p < 0.0001), myalgias (14.3% vs. 0.3%, p = 0.001) and fever (18.2% vs. 1.9%, p = 0.002). The serologic domain was detected in all cases (the most frequent were ANA in 17 and RF in nine cases) and morphologic domain (histology features) was positive in 6 out of 10 lung biopsies (lymphoid aggregates). Only patients with IPAF/IPF evolved to CTD at follow-up (10/22, 45.5%; six rheumatoid arthritis, one Sjögren’s and three scleroderma). The presence of IPAF was a positive prognostic determinant (HR 0.22, 95% CI 0.08–0.61, p = 0.003), whereas the isolated presence of circulating autoantibody did not impact prognosis (HR 1.00, 95% CI 0.67–1.49, p = 0.99). Conclusion The presence of IPAF criteria in IPF has a major clinical impact correlating with the risk of evolution to full blown-CTD during follow-up and identifying a subgroup of patients with a better prognosis.